Becoming Foucault : the Poitiers years / Michael C. Behrent. - Behrent, Michael C. (Intellectual History of the Modern Age, 2024)
Despite his enormous influence, little is known about Foucault's early years. Michael Behrent provides an account of this period while also offering an original interpretation of Foucault, showing that formative childhood experiences--the family medical profession, the provincial bourgeoisie, the German Occupation, and Catholic education--were decisive for the development of his thought". Provided by publisher.